PERANAN HAKIM DALAM MEWUJUDKAN PERADILAN YANG BEBAS DAN TIDAK MEMIHAK - Endang Retnowati (Perspektif, 2006)
Judge as one of the enforcer of law have role which of vital importance in execution of straightening of law in Indonesia, specially in realizing unbiased and free jurisdiction therefore judicial power to guarantee the execution of judicial power shall be guaranteed to free from side interreference of anywhere, but to avoid abuse needed by observation of compliance at regulation of values and invitation have to always be holded high and adhered judge responsibility not even to just state and society but also to the infinite Which Is Single The Most.